Utilization of waste polyethylene terephthalate as a reducing agent in the reduction of iron ore composite pellets - Polat, Gokhan; Birol, Burak; Saridede, Muhlis Nezihi (SPRINGER, 2014)
The increasing consumption of plastics inevitably results in increasing amounts of waste plastics. Because of their long degradation periods, these wastes negatively affect the natural environment. Numerous studies have been conducted to recycle and eliminate waste plastics. The potential for recycling waste plastics in the iron and steel industry has been underestimated; the high C and H contents of plastics may make them suitable as alternative reductants in the reduction process of iron ore. This study aims to substitute plastic wastes for coal in reduction melting process and to investigate their performance during reduction at high temperature. We used a common type of waste plastic, polyethylene terephthalate (PET), because of its high carbon and hydrogen contents. Composite pellets containing PET wastes, coke, and magnetite iron ore were reduced at selected temperatures of 1400 and 1450 degrees C for reduction time from 2 to 10 min to investigate the reduction melting behavior of these pellets. The results showed that an increased temperature and reduction time increased the reduction ratio of the pellets. The optimum experimental conditions for obtaining metallic iron (iron nuggets) were reduction at 1450 degrees C for 10 min using composite pellets containing 60% PET and 40% coke.
Keywords: polyethylene terephthalate (PET); waste recycling; reducing agents; iron ore pellets; ore reduction; Materials Science; Metallurgy & Metallurgical Engineering; Mining & Mineral Processing